العلاقة بين البدانة والتدخين وكثافة معدن العظم لدى النساء - حسن عبد الرزاق; الدو كاسر; شقوف كامل (Latakia University Journal -Medical Sciences Series, 2019)
أجريت هذه الدراسة لتقييم العلاقة بين مؤشر كتلة الجسم (Body Mass Index-BMI)، وتأثير التدخين على كثافة معدن العظم (Bone Mineral Density-BMD). تناولت الدراسة /121/ امرأة متوسط أعمارهن ± الانحراف المعياري سنة. خضعت جميع النساء لقياس الكثافة العظمية عند الفقرات القطنية (Lumbar Spine) LS(2-3-4)، بطريقة (Dual Energy X-ray Absorptiometry-DXA). كما تم حساب مؤشر كتلة الجسم وتم استجوابهن حول مدة التدخين وكميته. ثم تم ربط التقدم بالسن والـ BMI والتدخين بشكل مستقل بالـ BMD. كان هناك ارتباط إيجابي وثيق بين BMI و الـ BMD . كما كان تأثير التدخين السلبي على الـ BMD واضحاً فقط لدى مجموعة النساء ذوات الوزن الطبيعي . لكن ليس لدى فئتي الوزن الزائد والبدينات. كما كان الـ BMD للفقرات القطنية لدى المستمرات بالتدخين أخفض بنسبة 10% مما هو عند غير المدخنات، وكان لوقف التدخين تأثير هام إيجابي على الـ BMD. This study was performed to evaluate the relationship between Body Mass Index (BMI) and Bone Mineral Density (BMD) and the effect of smoking on BMD. This study included 121 women: these women benefited from the measurement of bone density of the lumbar spine (L2-L3-L4) by the DXA method. Also, BMD was calculated, and all women were asked about their history of smoking. The increased age and BMI were related to BMD independently. A strong, positive relation between BMT and BMD was confirmed (P = 0.033). The effect of passive smoking was noticeable in women of normal body weight (P = 0.007), but not in the two groups of (overweight and obese women). In addition, BMD in smoking women was 10% lower than it was in non-smokers; an important positive effect of cessating smoking on BMD was also detected.